1985
DOI: 10.1210/endo-116-2-677
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor in the Rabbit Liver and Apparent Translocation to the Nucleusin Vivo*

Abstract: The present study demonstrates that the liver of a mammal, the rabbit, contains an androgen receptor. Rabbit liver cytosol or purified nuclei were incubated with the radioactive androgen R-1881 (methyltrienolone). The cytosol of adult female rabbit liver contained androgen-binding sites of high affinity, Kd 0.9 nM, and a capacity of 7000 fmol/g liver or 79 fmol/mg cytosol protein. After partial purification by 35% ammonium sulfate precipitation (AS cytosol), the binding specificity pattern was consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…A marked decrease in the androgen binding sites in the soluble fraction with a concomitant in¬ crease in those in the insoluble fraction was found in HPOA, HMEA, and AP of the hens after admin¬ istration of the unlabelled in vivo, whereas the total number of binding sites did not change (Table 2). These findings are consistent with those in mammals (Isomaa et al 1982;Tezón et al 1982;Sheets et al 1985), and suggest that the androgenbinding component existing in the soluble fraction is transferred to the insoluble fraction when enough androgen is given in vivo in the same man¬ ner as proposed in mammals (Gorski et al 1986).…”
Section: Discussionsupporting
confidence: 86%
“…A marked decrease in the androgen binding sites in the soluble fraction with a concomitant in¬ crease in those in the insoluble fraction was found in HPOA, HMEA, and AP of the hens after admin¬ istration of the unlabelled in vivo, whereas the total number of binding sites did not change (Table 2). These findings are consistent with those in mammals (Isomaa et al 1982;Tezón et al 1982;Sheets et al 1985), and suggest that the androgenbinding component existing in the soluble fraction is transferred to the insoluble fraction when enough androgen is given in vivo in the same man¬ ner as proposed in mammals (Gorski et al 1986).…”
Section: Discussionsupporting
confidence: 86%
“…Likewise, studies on the rabbit liver by Sheets et al demonstrated that 1 h after administration of a high dosage of androgen almost all of the AR was detected in liver nuclei [34]. We considered this concept to be valid for human prostatic tissue as well.…”
Section: Discussionmentioning
confidence: 88%
“…The prostate has long been regarded as a classical androgen sensitive organ; more recently, the liver has been shown to contain the classical androgen receptor (Sheets, Aten, Kates et al 1985;Bannister et al 1985a,b (Boyden & Parmenter, 1983), their livers have morphological changes similar to those seen in the obese Zucker rat and they have reduced liver androgen receptor concentrations (Eagon, Porter, Francavi Ila et al 1985). In the human reduced levels of liver androgen receptor concentrations have been reported in two men with cirrhosis and associated hypogonadism (Bannister et al 1985b).…”
Section: Discussionmentioning
confidence: 99%